Anaphylaxis after consumption of wasp larvae in Reunion Island: a case report - Maillot, Adrien; Mathelin, Camille; Cazanove, Gregory; Marteau, Adrien (Frontiers in Allergy, 2023)
The practice of entomophagy is common in Asia, Africa, and South America and is now spreading to Europe and the United States. Entomophagy is not without risk since humans can develop allergic reactions to the ingested insects. Here we describe a case of anaphylaxis after consumption of Polistes olivaceus larvae in a 23-y-old man living in Reunion Island, a French overseas department where wasps and other insects are occasionally consumed as part of local traditions. The patient developed diffuse pruritus with facial edema, nausea, and vomiting 15 min after ingesting pan-fried wasp larvae during a dinner with two other people. He was taken to a local care center where he received two oral doses of antihistamines. Shortly after, he presented with shock and hemodynamic, respiratory, and neurological failure. He received a subcutaneous injection of adrenaline and was rapidly transferred to hospital for 12 h of monitoring, after which he was discharged without sequelae. The patient’s anaphylactic reaction may have been due only to the allergens contained in the ingested larvae or to cross-allergy. To our knowledge, this is the first reported case of anaphylaxis after consumption of Polistes olivaceus larvae. More generally, few cases of allergic reaction to ingested insects have been described in the literature.